Tuning the chaotropic effect as an assembly motif through one-electron transfer in a rhenium cluster. Issue 67 (30th July 2019) - Ivanov, Anton A.; Falaise, Clément; Landy, David; Haouas, Mohamed; Mironov, Yuri V.; Shestopalov, Michael A.; Cadot, Emmanuel
Abstract : As small change as one electron transfer within the hydrophilic rhenium cluster [Re6 Se8 (CN)6 ] 4−/3− induces dramatic alteration in supramolecular self-assembly properties with γ-cyclodextrin as a result of chaotropic effect driven process. Abstract : We report how only one electron transfer from the hydrophilic reduced cluster [Re6 Se8 (CN)6 ] 4− induces both a dramatic increase of the host–guest affinity with γ-cyclodextrin and a drastic alteration of the supramolecular dynamics. This striking behaviour, underlined by its thermochemical fingerprint, indicates that the self-assembly process is driven by a chaotropic effect.